Interventions to improve well-being among children and youth aged 6–17 years during the COVID-19 pandemic: a systematic review - Stephana J. Moss; Sara J. Mizen; Maia Stelfox; Rebecca Brundin Mather; Emily A. FitzGerald; Perri Tutelman; Nicole Racine; Kathryn A. Birnie; Kirsten M. Fiest; Henry T. Stelfox; Jeanna Parsons Leigh (BMC Medicine, 2023)
Abstract Background The COVID-19 pandemic is an example of a global infectious disease outbreak that poses a threat to the well-being of children and youth (e.g., physical infection, psychological impacts). The consequences of challenges faced during COVID-19 may be longstanding and newly developed interventions are being deployed. We present a narrative synthesis of available evidence from the first 2 years of the COVID-19 pandemic on the feasibility, accessibility, and effects of interventions to improve well-being among children and youth to inform the development and refinement of interventions relevant to post-pandemic recovery. Methods Six databases were searched from inception to August 2022. A total of 5484 records were screened, 39 were reviewed in full text, and 19 studies were included. The definition of well-being and the five domains of well-being as defined by the Partnership for Maternal, Newborn & Child Health and the World Health Organization in collaboration with the United Nations H6 + Technical Working Group on Adolescent Health and Well-Being were used. Results Nineteen studies (74% randomized controlled trials) from 10 countries were identified, involving a total of 7492 children and youth (age range: 8.2–17.2 years; 27.8–75.2% males) and 954 parents that occurred during the COVID-19 pandemic (March 2020 to March 2021). Nearly all interventions (n = 18, 95%) targeted health and nutrition, followed by connectedness (n = 6, 32%), while fewer studies targeted agency and resilience (n = 5, 23%), learning and competence (n = 2, 11%), or safety and support (n = 1, 3%). Five interventions (26%) were self-guided while 13 interventions (68%) were guided synchronous by a trained professional, all of which targeted physical and mental health subdomains within health and nutrition; one intervention (5%) was unclear. Conclusions Studies deploying synchronous interventions most often reported improved well-being among children and youth largely in the domain of health and nutrition, specifically physical and mental health. Targeted approaches will be crucial to reach sub-groups of children and youth who are most at risk of negative well-being outcomes. Further research is needed to determine how interventions that best supported children and youth early in the pandemic are different from interventions that are required now as we enter into the post-pandemic phase.